Determinants of unmet needs among Slovenian old population - Hlebec, Valentina (Zdravstveno varstvo, 2016)
Background. Population ageing has significant effects on societies. The organization of care for dependent old people is one of the key issues for ageing societies. The majority of care for homebound dependent old people in Slovenia is still performed by informal carers, even though the use of formal services has been increasing over the last 20 years. The proportion and characteristics of people with unmet needs are important for the development of long term care social policy. Method. The SHARE (Survey of Health, Ageing and Retirement in Europe) survey was used to assess the determinants of care arrangements and of unmet needs of the aging population in Slovenia. Multinomial regression analysis was used to evaluate individual and contextual determinants of care arrangements and unmet needs. Results.The proportion of older people with unmet needs is 4%. As expected, "needs" (Functional impairment OR=4.89, P=0.000, Depression OR=2.59, P=0.001) were the most important determinant, followed by the predisposing factor "age" (age OR 1.15, P=0.000) and two enabling factors, namely: "community setting" and "availability of informal care within household" (Urban areas OR=.47, P=0.021; Household size 3+ OR=2.11, P=0.030). Conclusion. This study showed that there are a proportion of older people in Slovenia with severe needs for care, which are being unmet. As shown by the importance of enabling factors, social policy should encourage the development of formal services in rural areas and elaborate policy measures for informal carers.
Keywords: Community care; Older people; Slovenia; Slovenija; Socialno skrbstvo; Starostniki